THE IMPLEMENTATION OF NATURE-BASED LEARNING IN ENHANCING EARLY CHILDHOOD COGNITIVE DEVELOPMENT FROM AN ISLAMIC EDUCATION PERSPECTIVE AT PERWARI PACITAN CHILDCARE CENTER - Susanti, Wiwit; Ahmadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of implementing Nature-Based Learning in improving early childhood cognitive development from an Islamic education perspective at Taman Penitipan Anak (TPA) Perwari Pacitan. This research employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group design. The subjects consisted of 12 children divided into two groups: the experimental group (A1) and the control group (A2), each consisting of 6 children. The research instrument was an observation sheet assessing cognitive development, including classification ability, problem-solving, concept understanding, and cause-effect reasoning. Data were analyzed using descriptive and inferential statistics with a t-test. The results showed that the average improvement in the experimental group was 8.3, higher than the control group at 3.8. The t-test result indicated a significance value of 0.000 (< 0.05), meaning there was a significant difference between the two groups. From an Islamic perspective, Nature-Based Learning also fosters spiritual awareness through reflection (tafakkur) and contemplation (tadabbur) of Allah’s creation. Therefore, Nature-Based Learning is effective in enhancing early childhood cognitive development holistically.